Carbon and conodont apatite oxygen isotope records from the Alengchu section in western Yunnan and their paleoclimatic and paleogeographic implications - Chen, Bo; Zhang, Mei-Qiong; Qie, Wen-Kun; Liang, Kun; Lu, Jian-Feng; Joachimski, Michael M.; Ma, Xue-Ping (Palaeoworld, 2024)
The Early Devonian witnessed dramatic changes in climate, ocean chemistry and faunal evolution. However, previous studies have relied mainly on records from North America and Europe (Prague Basin, Carnic Alps) and Australia, while data from China have been rarely reported, hindering robust δ13Ccarb chemostratigraphic correlation and evidence for the global significance of these events. Here, we report new carbon isotope and conodont apatite oxygen isotope records from the Alengchu section in western Yunnan which represents the most continuous Lower Devonian carbonate succession in China. Our study reports two positive δ13Ccarb excursions (Klonk isotope event, Lochkovian–Pragian isotope event) that can be correlated with published records globally. However, δ18Oapatite values are higher compared to coeval data from other sections. These higher values are interpreted as indicating cooler surface water temperatures as consequence of a persistent upwelling system at low latitudes which is consistent with the paleooceanographic circulation pattern reconstructed from combined evidence of climate modelling and geographic distribution of marine benthic ostracod assemblages.